Language Contact and the State of Multilingualism in the Linguistic Landscape of Tete Province in Mozambique (Journal of Humanities & Social Science (JHSS), 2023)
Mozambique is a multilingual country that adopted Portuguese as the language of official communication right from Independence Day in 1975. Later in the 1990s it adopted 19 Bantu languages as the media of instruction in lower education. This move opened an avenue for Bantu languages to be used in public domains in the country. Since the Metropolitan Maputo had been the centre of previous research of languages of public spaces, this paper looks at the language uses that unfold in the signposts of Tete Province to determine the manifestations of the Bantu languages in urban public spaces. Firstly, the findings pointed out that the monolingual and bilingual signage integrated the Portuguese structure of the noun phrase that puts modifiers before the head-noun, hence making the Portuguese structure dominant. Secondly, the findings reveal the use of international languages even in back streets of the Tete City. These two findings do not rule out the prestige that Bantu languages enjoy, mainly in the naming of shops. The predominance of Bantu languages in the names of shops indicate affiliation to ethnic groups. While the theory of multimodality helped to interpret the signposts, the social identity theory helped to arrive at the conclusion that Tete, the primary home of the Nyungwe, has remained the identity home of the people.MozambiqueReceived: 10th March 2023; Accepted: 17th April 2023; Revised: 9th July 2023